PENGARUH PENGGUNAAN PERMAINAN BALOK TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI RA MIFTAHUL JANNAH JELAT BAREGBEG CIAMIS - Jamilah, Ilah; Nugraha, Anggi Purwa; Mulyono, Nono (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
This study aims to determine the influence of playing blocks on early childhood’s fine motor skill. The study used Pre-experimental Design using the One Group Pretest-Posttest Design. The number of samples was 14 students, with a saturated sampling technique. The data collection technique uses a structured observation sheet and proceeded by SPSS Software. Then a hypothesis test is carried out using the Wilcoxon test. The results of the study showed that the early childhood’s fine motor skill scores before treatment were categorized Not yet Developed (BB) with the percentage 71.43%, and then were categorized Starting to Develop (MB) with the percentage 28.57%. After giving playing blocks treatment, the early childhood’s fine motor skill reached the category of Developing According to Expectation (BSH) with the percentage 85.71%, and then reached the category Very Well Developing (BSB) with the percentage 14.29%. Apart from that, after carrying out the Wilcoxon test, it was discovered that the sig. (2-tailed) of 0.001 < 0.05. Then it showed that the Pre-Test and Post-Test have a significant influence on the fine motor development of early childhoods, at which it is stated that if the sig. (2-tailed) < 0.05 then H0 is rejected and H1 is accepted. Therefore, it can be concluded that the use of playing blocks influenced towards the developmen of early childhood’s fine motor skill at RA Miftahul Jannah located in Baregbeg, Ciamis Regency.